Smoking bans, cigarette prices and life satisfaction - Reto Odermatt; Alois Stutzer (University of Basel, Center of Business and Economics (WWZ), 2013)
The consequences of tobacco control policies for individual welfare are difficult to assess. We therefore evaluate the impact of smoking bans and cigarette prices on subjective wellbeing by analyzing data for 40 European countries and regions between 1990 and 2011. We exploit the staggered introduction of bans and apply an imputation strategy to study the effect of anti-smoking policies on people with different propensities to smoke. We find that higher cigarette prices reduce the life satisfaction of likely smokers. Overall, smoking bans are not related to subjective well-being, but increase the life satisfaction of smokers who recently failed to quit smoking. The latter finding is consistent with cue-triggered models of addiction and the idea of bans as self-control devices.
Keywords: 330; Rauchen; Zigarette; Preis; Zufriedenheit; Europa